Vaccination as a cause of autism—myths and controversies. Issue 4 (31st December 2017) - Davidson, Michael
Abstract : Despite significant progress in the study of the epidemiology and genetics of autism, the etiology and patho-physiology of this condition is far from being elucidated and no curative treatment currently exists. Although solid scientific research continues, in an attempt to find explanations and solutions, a number of nonscientific and pure myths about autism have emerged. Myths that vaccines or mercury are associated with autism have been amplified by misguided scientists; frustrated, but effective parent groups; and politicians. Preventing the protection provided by vaccination or administration of mercury-chelating agents may cause real damage to autistic individuals and to innocent bystanders who as a result may be exposed to resurgent diseases that had already been "extinguished. " That such myths flourish is a consequence of the authority of scientific evidence obtained by scientific methodology losing ground to alternative truths and alternative science. This article presents a narrative of the origin of the myths around autism.